2023
DOI: 10.1158/2159-8290.cd-21-0502
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming Cancer into Antigen-Presenting Cells as a Novel Immunotherapy

Abstract: Therapeutic cancer vaccination seeks to elicit activation of tumor-reactive T cells capable of recognizing tumor-associated antigens (TAAs) and eradicating malignant cells. Here, we present a cancer vaccination approach utilizing myeloid lineage reprogramming to directly convert cancer cells into tumor reprogrammed-antigen presenting cells (TR-APCs). Using syngeneic murine leukemia models, we demonstrate that TR-APCs acquire both myeloid phenotype and function, process and present endogenous TAAs, and potently… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…This approach also applies to solid tumors, including sarcomas and carcinomas, and can be used in clinical settings by generating TR-APCs from patient specimens and stimulating autologous T cells. 210 Therefore, TR-APCs are a promising cancer vaccination strategy with broad implications for immuno-oncology.…”
Section: Cancer Vaccine Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…This approach also applies to solid tumors, including sarcomas and carcinomas, and can be used in clinical settings by generating TR-APCs from patient specimens and stimulating autologous T cells. 210 Therefore, TR-APCs are a promising cancer vaccination strategy with broad implications for immuno-oncology.…”
Section: Cancer Vaccine Therapymentioning
confidence: 99%
“…TR-APCs gain the ability to process and present TAAs, activate TAA-specific CD4+ and CD8+ T cells, and cause clonal expansion of cancer-specific T cells that build immune memory, ultimately leading to leukemia eradication. This approach also applies to solid tumors, including sarcomas and carcinomas, and can be used in clinical settings by generating TR-APCs from patient specimens and stimulating autologous T cells . Therefore, TR-APCs are a promising cancer vaccination strategy with broad implications for immuno-oncology.…”
Section: Extending the Boundaries Of Pancreatic Cancer Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Inducing LICs to differentiate into mature blood cells has long been recognized as a way to clear leukemia blasts from circulatory system 2 . Recently, a series of studies further showed that converting LICs to specialized myeloid antigen-presentation cells (such as dendritic cells and macrophages) can lead to long-lasting and specific anti-tumor immune responses, possible by enhancing neoantigen presentation and recognition by cytotoxic T lymphocytes 3, 4 . Thus, directed differentiation or cellular reprogramming of leukemia blasts holds the potential to not only abolish leukemogenesis but also serve as the basis for developing novel anti-cancer vaccines 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Because leukemic blasts resemble developmentally arrested HSPCs 2, 6, 7 , normal hematopoietic lineage-determining TFs have been exploited to direct maturation of leukemia blasts with the expectation that leukemic blasts would assume the trajectory of normal hematopoietic cells towards maturation 8 . Indeed, this is the basis for the development of TF cocktails to, for example, reprogram various leukemia cells to nonleukemic macrophages using C/EBP α and PU.1/SPI1 3, 4 or to classical Dendritic cells using PU.1, IRF8, and BATF3 9 . However, normal hematopoiesis is controlled by densely interconnected transcriptional circuits and the functionality of TFs is critically dependent on the accessible chromatin landscape within the cell.…”
Section: Introductionmentioning
confidence: 99%